An investigation into the Use of Metacognitive Strategies in Translating Pragmatic Texts The Case of First Year Master Students at University of M’sila - Firdaws NOUR, Chaima BEN HAMED (My University, 2020)
Abstract Translating pragmatic texts is considered as a challenging task for most EFL learners, due to the lack of knowledge about the crucial aspects and requirements of the pragmatic translation. This study attempts to investigate the use of metacognitive strategies in translating pragmatic texts by master one EFL learners at Mohammed Boudiaf University of M’sila, as well as, to examine their employment of these strategies and to figure out the frequently used category of the three main MSs, .i.e. planning, monitoring, and evaluating strategy, in pragmatic translation. This study aims to raise learners and teachers’ awareness about the importance of the use of MSs in improving translation process and products. In this descriptive study, the data were gathered by means of a prospective questionnaire was distributed to 32 M1 students from both specialities; Linguistics and English Literature, to investigate their awareness about the MSs, a pragmatic text translating test was handed for 30 students of M1 English Literature beside a retrospective questionnaire to investigate the application and employment of MSs in translating pragmatic texts by learners. The data obtained from the research tools were analyzed quantitatively and qualitatively. The findings show that M1 students at Mohammed Boudiaf University of M’sila are using the MSs in translation at a medium level; yet, they are unaware of their use. In translating pragmatic texts, the results indicate that M1 students used all the three categories of MSs. Compared to other MSs, planning was the most used strategy among students when translating the pragmatic text
Keywords: Keywords: Translation, metacognitive strategies, pragmatic texts.